Aggregation of Washed Platelets from Non-Anticoagulated Human Blood Is Not Reversible - Bowry, S K; Müller-Berghaus, G (Thrombosis and Haemostasis, 1986)
Most of the knowledge acquired on platelet function and biochemistry has been obtained from platelets prepared from blood anticoagulated with sodium citrate. Using washed platelets from human blood (PNB) to which no anticoagulants were added, we report on responses not observed with platelets prepared from citrate-anticoagulated blood. Native blood was passed rapidly (within 5 min of venepuncture) through a Sephadex G-25/G-50 column to remove divalent ions and thus prevent coagulation. Platelets were separated from the gel-filtered blood by differential centrifugation. Responses of PNB to thrombin, collagen, calcium ionophore, ristocetin, release of 14C-5hydroxytryptamine and p-thromboglobulin, and generation of thromboxane A2 were similar to those observed for citrated platelets. Comparison of PNB with thrombin-treated platelets, which demonstrate an increase of platelet factor 3 activity, a reduction of the adenylate energy charge and an impairment of clot retraction, indicated the absence of platelet activation. Unlike citrated platelets, however, aggregation of PNB in response to ADP was irreversible in the presence of Ca2+ and fibrinogen, even at concentrations as low as 0.2 μM ADP, with aggregation taking up to 25 times longer to reach the same extent of aggregation as for citrated platelets. PNB did not aggregate to epinephrine even in the presence of Ca2+ and fibrinogen. Sodium citrate impaired ADP-induced aggregation and clot retraction of PNB. Thus citrate affects platelet function and may cause changes resulting in the unphy-siological behaviour and responses of platelets.
Keywords: Platelets; Citrate; Activation